A Statewide Study of Perceptions of Directors on the Availability of Online Student Support Services at Postsecondary Institutions - Brown, Victoria S.; Strigle, Josh; Toussaint, Mario (Online Learning, 2020)
As a state university system planned for growth in the availability of distance education degrees, the presidents and the provosts decided to include consideration for the availability of student support services. To ensure availability of student support services for online students, college and university systems in the state developed and implemented a self-reporting tool, the Online Student Support Scorecard to measure the availability of those services at both the college and the university levels. Although institutions were offering many of the services identified in the scorecard as essential, institutions were struggling to provide some of the services. Differences also were identified between the types of services available at the state college system compared with the university system.